Soluble Starch Synthase III-1 in Amylopectin Metabolism of Banana Fruit: Characterization, Expression, Enzyme Activity, and Functional Analyses - Miao, Hongxia; Sun, Peiguang; Liu, Qing; Jia, Caihong; Liu, Juhua; Hu, Wei; Jin, Zhiqiang; Xu, Biyu (Frontiers in Plant Science, 2017)
Soluble starch synthase (SS) is one of the key enzymes involved in amylopectin biosynthesis in plants. However, no information is currently available about this gene family in the important fruit crop banana. Herein, we characterized the function of MaSSIII-1 in amylopectin metabolism of banana fruit and described the putative role of the other MaSS family members. Firstly, starch granules, starch and amylopectin content were found to increase during banana fruit development, but decline during storage. The SS activity started to increase later than amylopectin and starch content. Secondly, four putative SS genes were cloned and characterized from banana fruit. Among them, MaSSIII-1 showed the highest expression in banana pulp during fruit development at transcriptional levels. Further Western blot analysis suggested that the protein was gradually increased during banana fruit development, but drastically reduced during storage. This expression pattern was highly consistent with changes in starch granules, amylopectin content, and SS activity at the late phase of banana fruit development. Lastly, overexpression of MaSSIII-1 in tomato plants distinctly changed the morphology of starch granules and significantly increased the total starch accumulation, amylopectin content, and SS activity at mature-green stage in comparison to wild-type. The findings demonstrated that MaSSIII-1 is a key gene expressed in banana fruit and responsible for the active amylopectin biosynthesis, this is the first report in a fresh fruit species. Such a finding may enable the development of molecular markers for banana breeding and genetic improvement of nutritional value and functional properties of banana fruit.